Incorporating measurable ('minimal') residual disease-directed treatment strategies to optimize outcomes in adults with acute myeloid leukemia. Issue 7 (2nd July 2016) - Pettit, Kristen; Stock, Wendy; Walter, Roland B.
Abstract: Curative-intent therapy leads to complete remissions in many adults with acute myeloid leukemia (AML), but relapse remains common. Numerous studies have unequivocally demonstrated that the persistence of measurable ('minimal') residual disease (MRD) at the submicroscopic level during morphologic remission identifies patients at high risk of disease recurrence and short survival. This association has provided the impetus to customize anti-leukemia therapy based on MRD data, a strategy that is now routinely pursued in acute promyelocytic leukemia (APL). While it is currently uncertain whether this approach will improve outcomes in AML other than APL, randomized studies have validated MRD-based risk-stratified treatment algorithms in acute lymphoblastic leukemia. Here, we review the available studies examining MRD-directed therapy in AML, appraise their strengths and limitations, and discuss avenues for future investigation.